BRAF, NRAS, KIT, TERT, GNAQ/GNA11 Mutation Profile and Histomorphological Analysis of Anorectal Melanomas: A Clinicopathologic Study - Orhun Cig TASKIN; Sule OZTURK SARI; Ismail YILMAZ; Ozge HURDOGAN; Metin KESKIN; Nesimi BUYUKBABANI; Mine GULLUOGLU (Federation of Turkish Pathology Societies, 2023)
Objective: Primary anorectal melanomas (AMs) are uncommon neoplasms with aggressive behavior. Molecular profile and clinicopathologic features of AMs are still not well established. In this study, we aimed to investigate BRAF, NRAS, KIT, TERT, and GNAQ/GNA11 mutation status and clinicopathologic features of AMs. Material and Method: All diagnostic slides of 15 AMs were reviewed. Histopathological and follow-up information were documented. Mutations in exon 15 of the BRAF gene; exons 2 and 3 of the NRAS gene; exons 9, 11, 13, 17, and 18 of the KIT gene; and exons 4 and 5 of the GNAQ/GNA11 genes and mutations in the promoter region of the TERT gene (chr.5, 1,295,228C>T and 1,295,250C>T) were analyzed. Results: BRAF(V600E) and KIT(V555I and K642E) mutations were observed in one (7%) and two cases (14%), respectively. NRAS, TERT and GNAQ/GNA11 mutations were not detected. The mean age was 65. Patients presented with rectal mass, rectal bleeding, pain, and weight loss. 73% of the lesions were macroscopically polypoid. The most common tumor cell type was epithelioid. Mean tumor thickness was 10.4 mm. One third of the cases lacked pigmentation. In situ melanoma was present in one third of the cases. Among 14 patients with follow-up data, 12 succumbed to disease. The mean overall survival was 36 months. Conclusion: AMs are uncommon tumors with dismal survival, usually occurring in the elderly in various gross and microscopic appearances. In terms of molecular profile, BRAF and KIT mutations are rarely detected. Profiling of larger cohorts is required to elucidate the pathogenesis and to identify potential molecular indicators that may contribute to the development of individualized targeted therapies.